Strengthening the Pancasila Student Profile in Forming Student Character at SDIT Permata Bunda III Bandar Lampung - Nurani, Nurani; Hijriyah, Umi; Mas Ayu, Sovia (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The Project for Strengthening the Pancasila Student Profile (P5) was implemented to support character development through project-based learning. This study aimed to describe the management of P5 at SDIT Permata Bunda III Bandar Lampung. A qualitative descriptive design was employed, involving 1 principal, 3 P5 coordinators, 6 teachers, and 20 students selected through purposive sampling. Data were collected through interviews, observations, and document review, and were analyzed using Miles and Huberman’s model of data condensation, display, and conclusion drawing. The findings showed that P5 was managed through four stages: planning, organizing, implementation, and evaluation. Planning was carried out collaboratively by aligning project themes with Pancasila and Islamic values. Organizing involved distributing roles among coordinators, teachers, and parents. Implementation used project-based learning activities, such as environmental care and social charity projects. Evaluation was conducted through rubrics and student reflections. Records indicated a 35% decrease in disciplinary incidents and increased student participation. The study concluded that effective management practices and value integration supported improvements in students’ character development and highlighted the need to strengthen leadership and teacher competence in managing P5.